1973
DOI: 10.1128/jb.115.3.816-823.1973
|View full text |Cite
|
Sign up to set email alerts
|

Three Kinds of Controls Affecting the Expression of the glp Regulon in Escherichia coli

Abstract: Three kinds of control mechanisms govern the expression of the members of the glp regulon for glycerol and sn-glycerol 3-phosphate (G3P) catabolism in Escherichia coli K-12: specific repression by the product of the glpR gene; catabolite repression; and respiratory repression (the effect exerted by exogenous hydrogen acceptors). The operons of the glp system show different patterns of response to each control. By growing in parallel a mutant strain with temperature-sensitive repressor (glpRt8) and an isogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 40 publications
0
36
1
Order By: Relevance
“…2A). Catabolite repression of glpFKX operon (Freedberg and Lin, 1973;Weissenborn et al, 1992), may account for the lack of induction by glycerol in LB medium.…”
Section: Expression Of Glpfkx Operon Is Positively Regulated By Transmentioning
confidence: 99%
“…2A). Catabolite repression of glpFKX operon (Freedberg and Lin, 1973;Weissenborn et al, 1992), may account for the lack of induction by glycerol in LB medium.…”
Section: Expression Of Glpfkx Operon Is Positively Regulated By Transmentioning
confidence: 99%
“…1B). Previous in silico predictions had suggested that the promoters of the glp regulon share a common regulatory motif in different Gram-negative bacteria (Freedberg and Lin, 1973;Schweizer and Po, 1996;Danilova et al, 2003) and that glpR, glpK and glpF might form an operon (Mao et al, 2009). However, the sequence coverage plots demonstrated that this is not the case, as two distinct transcriptional units were clearly identified; one of them encompassed glpF and glpK, whereas glpD was independently transcribed.…”
Section: Physiology Of P Putida Kt2440 Growing On Different C Sourcesmentioning
confidence: 99%
“…In the glycerol kinase assay, phosphorylation of glycerol was coupled to reduction of NAD + by NAD-dependent L-c~-G3P dehydrogenase from rabbit muscle. The assay was performed at 25°C essentially as described by Freedberg and Lin [7]. By using a buffer with pH 9.0 instead of 9.5, more reproducible results were obtained.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…The glp genes are repressed to various degrees by a protein repressor and require G3P for full expression. The glp genes are also subject to glucose and catabolite repression [7,8]. In other bacteria than E. coli relatively little is known about the organization and regulation of genes involved in glycerol catabolism.…”
Section: Introductionmentioning
confidence: 99%